2023
DOI: 10.1111/plb.13554
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of soil acidification and ammonium nitrogen content in tea plantations by long‐term use of organic fertilizer

Abstract: Soil acidification is common in some Chinese tea plantations, which seriously affected growth of tea trees. Hence, it is essential to explore soil remediation in acidified tea plantations for sustainable development of the tea industry. We sought to determine how different fertilizers affect acidified soil and their N transformation in tea plantations. Different fertilizers were used on acidified tea plantation soils for 4 years (2017–2021), and changes in soil pH, indices related to soil N transformation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…We found that soil pH increased and the available nutrient content increased after pruning tea tree, while the total nutrient content decreased instead. It has been reported that soil pH is closely related to nutrient cycling in the soil, and increasing soil pH is favorable to increase the available nutrient content in the soil, which is conducive to promoting the growth of tea trees and increasing tea yield [31,32]. This study also found that the total nutrient content of the soil decreased after the pruning of tea trees.…”
Section: Discussionsupporting
confidence: 62%
“…We found that soil pH increased and the available nutrient content increased after pruning tea tree, while the total nutrient content decreased instead. It has been reported that soil pH is closely related to nutrient cycling in the soil, and increasing soil pH is favorable to increase the available nutrient content in the soil, which is conducive to promoting the growth of tea trees and increasing tea yield [31,32]. This study also found that the total nutrient content of the soil decreased after the pruning of tea trees.…”
Section: Discussionsupporting
confidence: 62%
“…It was shown that with the increase of soil pH (3.29 to 5.32), AN, AP and AK content in the rhizosphere soil of tea tree increased from 35.23 to 91.38 mg/kg, from 3.13 to 15.12 mg/kg and from 49.25 to 127.95 mg/kg, respectively. It has been reported that there is a significant correlation between soil pH and nutrient availability in the rhizosphere soil of tea trees, and that an appropriate increase in soil pH is conducive to promoting nutrient transformation in the rhizosphere soil of tea trees, increasing the content of available nutrients and thus enhancing root activity of tea trees, and promoting tea tree growth ( Jia et al., 2023 ; Ye et al., 2023c ). It can be seen that increasing soil pH can effectively promote soil nutrient transformation and increase the available nutrient content of rhizosphere soil of tea trees.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, soil acidification also causes changes in the fertility of soil, especially in rhizosphere soil, which affects the uptake of nutrients by plants, leading to a decrease in plant yield or quality [19]. This change may be due to the acidification of soil altering the amount and type of plant root secretions which, in turn, affects the colonization of the rhizosphere soil by microorganisms and the soil enzyme activities, especially those related to nutrient cycling, altering the nutrient contents of a plant's rhizosphere soil and affecting plant yield and quality [20,21]. However, there are few reports on the effects of soil acidification on the fertility of rhizosphere soil and the quality of tea aroma, especially the effect of the soil fertility index on the aroma of tea evaluated using the OAV value method.…”
Section: Introductionmentioning
confidence: 99%